STEM AS A TECHNOLOGY FOR THE FORMATION OF THE CONCEPT OF "ENERGY" IN A SCHOOL PHYSICS COURSE - Ramankulov Ш.Ж.; Bitibaeva Ж.М.; Kurbanbekov Б.А.; Mussakhan Н.; Pattayev А. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2023)
Today, technology is developing rapidly. For the effective implementation of the educational process, especially in the integrative study of natural sciences, many innovative technologies can be used. Currently, educational materials can be provided using various digital forms. This study briefly describes the trends in the needs and interests of students in the school physics course in relation to educational materials, especially in relation to the topic of energy. The purpose of the study is to identify the expected challenges that teachers and students face when implementing integrated STEM learning to facilitate their learning and learning of the concept of energy in high school. In the course of the study, the analysis of scientific literature, textbooks and curricula of the school physics course was carried out. Work was also carried out on the selection of STEM elements, digital educational resources. These materials were included in the educational process and control works were organized among students on energy topics. The results of the study showed that STEM technology makes it possible to enrich students with activities aimed at developing scientific knowledge related to the concept of energy. Based on the data obtained, it can be seen that students are more interested in providing auxiliary educational materials, such as digital educational resources, when studying the laws of conservation and transformation of energy. The data obtained as a result of the study are presented for use in organizations of higher and secondary education, and these results serve as the basis for research in a new direction in the educational field of physics.